Isolation and Identification of two bioactive compounds from basidiomycetes fungus Coprinus sp. - Kawther T. Khalaf (University of Thi-Qar Journal of Science, 2019)
The fungus Coprinus sp. was isolated and cultivation in laboratory on two PDA medium with some growthinduction .Two bioactive chemical compounds were isolated and purified from mycelial culture of Coprinus sp. byusing potato dextrose agar and potato dextrose broth . The two compounds were identified by using GC-mass technique .The molecular weight of purified compounds 1 and 2 were 352 KD and 388 KD respectively and chemical formula ofcompound 1 is C21H24N2O3 which isolated from solid medium while compound 2 is C24H26O4 which isolated frombroth medium . The antibacterial activity of the purified compounds against three bacterial species E. coli , Proteus sp.and S. aureus were tested by using a disk diffusion agar method reaching to 40 , 30 , 20 for compound 1and 37, 25 , 17mm for compound 2.